The Impact of Diabetes on HF - Mosley, Mary (MD Conference Express, 2014)
Type 2 diabetes mellitus (T2DM) has been described as a possible risk factor for heart failure (HF). Several different pathways may contribute to the increased risk for HF in patients with T2DM, including the increased prevalence of coronary artery disease or other risk factors for HF, because traditional risk factors for HF are more prevalent in patients with T2DM. This article discusses these risks, the effect of HF drugs in T2DM, and antidiabetic drugs in HF.